Programming for Linguists: JavaTM Technology for Language Researchers - Hammond, Michael (USA: Blackwell Publishing)
This book includes over one hundred carefully constructed sample programs that introduce new concepts simply but also accomplish tasks necessary for anyone who works with language as data.
Includes Bibliographic references and index.
Keywords: Java TM Programming-- Linguists--Language Researchers